An investigation of the internet generation customer loyalty: an empirical study in Indonesia mobile services - Yacob, Syahmardi; Johannes, Johannes; Edward, Edward; Sulistiyo, Urip; Mukminin, Amirul (Business: Theory and Practice, 2023)
The study aims to investigated of iGen customer loyalty model that effected by service quality, culture, loyalty program and trust trough customer satisfaction. Following the conceptual model, an inclusive set of hypotheses have been developed. The demanded data were collected from 663 samples using an online survey, and Structural Equation Model with Smart Partial Least Square was applied to test the model and hypotheses. The research found that service quality, culture,loyalty programs, and trust are combined to predict customer loyalty. Trust and loyalty programs exert a more powerful impact on customer loyalty than service quality and culture variables. Customer satisfaction acts as a mediator in the relationship between service quality, loyalty programs, customer trust, and customer loyalty. The results have some critical academic and professional implication for determining the model of consumer loyalty and the internet generation (iGen) in mobile communication services. The study can be used as a part model in formulating a marketing strategy operation that has a competitive advantage in the mobile communication services in Indonesia.